2012
DOI: 10.1007/s11999-011-2139-9
|View full text |Cite
|
Sign up to set email alerts
|

Is the Dislocation Rate Higher after Bipolar Hemiarthroplasty in Patients with Neuromuscular Diseases?

Abstract: Background Patients with neuromuscular disease reportedly have a higher incidence of postoperative dislocation after bipolar hemiarthroplasty. Although the literature has focused on a high prevalence of preoperative neurologic conditions in patients who had dislocations after bipolar hemiarthroplasties, the relative incidence of dislocation in patients with neuromuscular disease and without is unclear. Questions/purposes We therefore (1) asked whether the incidence of postoperative dislocation after bipolar he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
(62 reference statements)
1
12
1
Order By: Relevance
“…Some studies have suggested that these patients had high risks of hip dislocation ranging from 11% to 45% after bipolar hemiarthroplasty for hip fracture [3,22,24]. In contrast, Suh et al [23] and we observed similar proportions of dislocation in patients with and without neuromuscular disease, but their study and our study might lack enough patients with neuromuscular conditions to really test the question with adequate statistical power.…”
Section: Discussioncontrasting
confidence: 60%
“…Some studies have suggested that these patients had high risks of hip dislocation ranging from 11% to 45% after bipolar hemiarthroplasty for hip fracture [3,22,24]. In contrast, Suh et al [23] and we observed similar proportions of dislocation in patients with and without neuromuscular disease, but their study and our study might lack enough patients with neuromuscular conditions to really test the question with adequate statistical power.…”
Section: Discussioncontrasting
confidence: 60%
“…The incidence of dislocation after hemiarthroplasty has been reported as 1.5% to 13.4%. 22,[32][33][34][35] Although the reason for dislocation in this population includes a combination of factors, elderly patients with multiple medical comorbidities may be unable to comply with the positional restrictions prescribed by surgeons using the posterior and anterolateral approaches. The dislocation rate in the current study was 3% (n=3), which is consistent with previously reported rates after hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rigidity and cognitive decline associated with Parkinson's disease, dislocation, even with hemiarthroplasty, remains a concern [33]. Coughlin and Templeton [6] reported a dislocation rate of 37% in patients with Parkinson's disease and hemiarthroplasty for displaced femoral neck fractures.…”
Section: Discussionmentioning
confidence: 99%